2019
DOI: 10.1515/for-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

From Wedge Issue to Partisan Divide: The Development of Immigration Policy Opinion after 2016

Abstract: President Trump won an Electoral College majority in 2016 bolstered by voters who supported him, but not the previous nominee, Mitt Romney. Evidence suggests that a campaign promising a more restrictive immigration policy was the key to this improved performance among cross-pressured voters. In the months since inauguration day 2017, however, voters did not remain unaware of the administration’s programmatic steps on immigration and the opposition they encountered. I interpret evidence from a panel survey to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The 2016 U.S. presidential election was stressful for many individuals (American Psychological Association [APA], 2017), but particularly for immigrants given the centrality of immigration policy during the election campaign (Agbafe, 2016;Gimpel, 2017). A majority (56%) of Latinos, the largest immigrant population in the United States (American Community Survey, 2017), reported that the outcome of the election was a "very" or "somewhat" significant source of stress (APA, 2017).…”
mentioning
confidence: 99%
“…The 2016 U.S. presidential election was stressful for many individuals (American Psychological Association [APA], 2017), but particularly for immigrants given the centrality of immigration policy during the election campaign (Agbafe, 2016;Gimpel, 2017). A majority (56%) of Latinos, the largest immigrant population in the United States (American Community Survey, 2017), reported that the outcome of the election was a "very" or "somewhat" significant source of stress (APA, 2017).…”
mentioning
confidence: 99%
“…One argument with respect to our findings of responsiveness to the partisanship of the president is that it is driven mostly by responsiveness to Trump, who utilized immigration as a campaign issue to a greater extent than previous presidents (Gimpel, 2017). Therefore, it is possible that our results for post‐REAL ID responsiveness, which encompass only three presidents: George W. Bush, Obama, and Trump, are driven by the unusual character of Trump's issue focus.…”
Section: Methodsmentioning
confidence: 86%
“…Based on the work of Hillygus and Shields (2008), we also focus on typical wedge issues to examine closely how these more contentious issues are used in targeted messages. Based on Gimpel (2019), we focus on the issue of immigration, as he suggested that since 2016, voters “began to align their policy views with the positions of their favored political parties” (p. 467) and that “[t]he association between party identification and immigration policy views reaches a local peak by 2018” (Gimpel, 2019, p. 473). Furthermore, we focus on divisive issues, based on previous work by Hillygus and Shields (2008) and on the issues which were in 2018 of importance in the public debate.…”
Section: Targeting In the Political Arenamentioning
confidence: 99%